Regeneration and Preliminary Characterization of Asian and African Okra (Abelmoschus spp.) Germplasm - Sani, Idi Saidou; Grema, Moustapha; Sanjeet, Kumar; Yacoubou, Bakasso; Mahamane, Ali (European Scientific Journal, ESJ, 2019)
The morphological variability of 56 okra (Abelmoschus spp.) Accessions was evaluated over two years (2008 and 2009). Ten (10) agromorphological characters were evaluated in the Sadoré station in Niger. The hierarchical ascendant classification (CAH) and the discriminant factor analysis (AFD) revealed four groups (GI, GII, GIII and GIV). The accessions in groups I and IV have high values of Lfm, Dfm, Height, and Nloc, Nepi and cons by low values. However, Flo or Fruct values are relatively higher in accessions of group III and IV than in accessions of group I. Similarly, accessions of group II have higher values in Flo and Fruct than group II. However, accessions of group II are much later in terms of which accessions in group I, which, in turn, have lower values in Flo and Fruct, so these are compared to those of Group II. The results show that the most discriminating variables that make it possible to describe Variability among the groups identified are the diameter of mature fruits (Dfm), Plant height (Height) and branch of plant number (Nbrch). The characters analyzed can thus constitute basic criteria to differentiate accessions from other regions of West Africa and serve for a study of variability between the remains of okra accessions collected in Niger. Opportunities for improvement can also be considered to identify varieties that have a high adaptive potential due to climate change.